2010
DOI: 10.1017/s1368980009992953
|View full text |Cite
|
Sign up to set email alerts
|

A computerised tailored intervention for increasing intakes of fruit, vegetables, brown bread and wholegrain cereals in adolescent girls

Abstract: Objective: To evaluate the effectiveness of a computer-generated tailored intervention leaflet compared with a generic leaflet aimed at increasing brown bread, wholegrain cereal, fruit and vegetable intakes in adolescent girls. Design: Clustered randomised controlled trial. Dietary intake was assessed via three 24 h dietary recalls. Setting: Eight secondary schools in areas of low income and/or high ethnic diversity, five in London and three in the West Midlands, UK. Subjects: Girls aged 12-16 years participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(45 citation statements)
references
References 27 publications
0
45
0
Order By: Relevance
“…Participant age ranged from nine to seventeen. Four studies focused on twelve- to fourteen-year-olds [ 8 9 , 11 , 17 ], four included older participants (fifteen- to seventeen-year-olds) [ 10 , 12 13 , 18 ], and three encompassed younger ones [ 13 14 , 16 ]. All studies included participants from developed countries, but five interventions targeted specific populations such as low-income groups, ethnic minorities, or minority females or males [ 11 14 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participant age ranged from nine to seventeen. Four studies focused on twelve- to fourteen-year-olds [ 8 9 , 11 , 17 ], four included older participants (fifteen- to seventeen-year-olds) [ 10 , 12 13 , 18 ], and three encompassed younger ones [ 13 14 , 16 ]. All studies included participants from developed countries, but five interventions targeted specific populations such as low-income groups, ethnic minorities, or minority females or males [ 11 14 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sample sizes ranged from 87 to 1298 participants, and three studies observed over 800 adolescents [ 8 , 10 , 12 ]. Of the eleven interventions, two were randomized controlled trials [ 11 , 17 ], five were cluster randomized controlled trials [ 9 10 , 13 , 15 , 18 ], and four used a quasi-experimental design [ 8 , 12 , 14 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…In general, adherence to clinical guidelines depends on the attitude of the health care professional, the guideline, the organizational context and social and cultural factors (Cabana et al, ; Grol and Grimshaw, ; Cahill et al, ). The effectiveness of guideline implementation is enhanced if the strategy is appropriate for the innovation, setting and target group and includes assessment of current practice and barriers for adherence (Grol et al, ; Rees et al, ). Therefore, we designed the ICU DElirium in Clinical PracTice Implementation Evaluation (iDECePTIvE) study, which is a prospective multicentre study in the Netherlands aimed at a multifaceted implementation program to increase adherence to ICU delirium guidelines and to evaluate effects of the programme on processes of care and clinical outcomes (Ista et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…42 A final characteristic of successful interventions to increase WG intake was the use of social media and the Internet. 22,43 Internet-based interventions were convenient and flexible and enabled the instantaneous and inexpensive distribution of nutrition education; many people already used it as a source of health information. 44 Any WG intervention needs a coordinated and comprehensive integrated contribution from all sectors (academia, government, trade and industry, and advocacy groups), disciplines (from plant geneticists through growers, product developers, distributors, and food service personnel), and, importantly, consumers.…”
Section: Taggedh1 Taggedend Discussionmentioning
confidence: 99%